2017
DOI: 10.1080/00016357.2017.1286034
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of children’s oral health-related quality of life after dental general anaesthesia treatment

Abstract: This longitudinal study showed a sustained improvement in the children's OHRQoL six months after their DGA treatment. Post-operative parental ratings of their child's oral health were higher after the DGA treatment, but the children exhibited insufficient oral hygiene and new caries lesions. An appropriate follow-up system for children receiving DGA treatment with special focus on preventive care is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 22 publications
8
28
0
6
Order By: Relevance
“…In accordance with the inclusion and exclusion criteria, 11 articles were excluded. After evaluating the texts comprehensively, all 21 articles were included in the meta‐analysis . Within the same publication, one study contributed to the meta‐analysis twice because both the ECOHIS and COHRQoL questionnaires were used .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the inclusion and exclusion criteria, 11 articles were excluded. After evaluating the texts comprehensively, all 21 articles were included in the meta‐analysis . Within the same publication, one study contributed to the meta‐analysis twice because both the ECOHIS and COHRQoL questionnaires were used .…”
Section: Resultsmentioning
confidence: 99%
“…After evaluating the texts comprehensively, all 21 articles were included in the meta-analysis. 3,14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Within the same publication, one study contributed to the meta-analysis twice because both the ECOHIS and COHRQoL questionnaires were used. 37 In addition, within the same publication, another study utilised the COHRQoL questionnaire in two different groups.…”
Section: Literature Searchmentioning
confidence: 99%
“…Untreated oral diseases and negative treatment experiences can adversely affect the quality of life. Jabarifar et al and Jankauskiené et al observed an improvement in the children's quality of life after dental rehabilitation under general anesthesia. The improvement in our case was reflected on the patient's acceptance to continue the prosthetic treatment and space management on the dental chair.…”
Section: Discussionmentioning
confidence: 99%
“…Lithuanian children with high ECC experience have severe dental problems, poor quality of life, and undergo multiple caries treatments and extractions under general anaesthesia [15]. Moreover, new caries lesions often develop with insufficient oral hygiene following dental treatment under general anaesthesia [36].…”
Section: Children In Lithuaniamentioning
confidence: 99%